King's cage - Aveyard, Victoria (2017)
With Mare powerless as a prisoner of Maven Calore, the boy she once loved, her rebel Reds continue to organize and train as they prepare for war, while exiled prince Cal sets out to rescue Maven from captivity.
Keywords: Ability -- Juvenile fiction; Blood -- Juvenile fiction; Princesses -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Ability -- Fiction; Blood -- Fiction; Princesses -- Fiction; Government, Resistance to -- Fiction; Young adult fiction; Fantasy fiction; Science fiction